Pengaruh Edukasi Media Podcast Dan Video Animasi Terhadap Pengetahuan Gizi Lebih Remaja Usia 16-18 Tahun Di SMA PGRI 3 Bogor - Adrianto, Bayu; Ilmi, Ibnu Malkan Bakhrul; Syah, Muhammad Nur Hasan; Sufyan, Dian Luthfiana (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Background: The nutritional status of overweight and obesity worldwide has almost tripled since 1975. In 2016, more than 340 million children and adolescents aged 5-19 years experienced overnutrition and obesity. Most nutritional problems can be avoided if an individual has good knowledge about nutrition and regulates eating. Nutrition education is provided to increase the level of knowledge and use interesting media so that the educational material to be delivered can be received more easily. Objective: Knowing the difference in the level of knowledge about overweight in adolescents 16-18 years before and after being given education with videos and podcasts. Method : Quasy experimental study with pre-post-test group design involving 80 students in class X and XI which choosed by cluster random sampling. Knowledge data collected with online method. Result :there are a difference knowledge with the use of nutrition education media through podcasts (p=0.000) and animated videos (p=0.000). Conclusion: There are differences in the level of knowledge about overweight in adolescents 16-18 years before and after being given education with videos and podcasts